The Potential Of Mangrove Ecotourism in Pagatan Besar Village, Takisung Sub-District, Tanah Laut Regency South Kalimantan Province - Primayoga, Reiga Primayoga; Arisanty, Deasy; Alviawati, Eva; Muhaimin, Muhammad; Saputra, Aswin (Journal of Indonesian Tourism and Development Studies, 2024)
This study aims to identify the potential of mangrove ecotourism and formulate appropriate development strategies in Pagatan Besar Village, Takisung District, Tanah Laut Regency, South Kalimantan Province. The method used is a descriptive quantitative approach, with data collection conducted through purposive sampling, involving 63 tourists, 23 residents, and 14 related parties. The analysis was carried out using the ADO-ODTWA and SWOT approaches. The results of the ADO-ODTWA analysis indicate that the mangrove area in Pagatan Besar Village has high potential for development as an ecotourism destination, based on from its natural attractions, ease of access, and visitor enthusiasm. Based on the SWOT analysis, the position of the development strategy falls in quadrant I, indicating that strengths such as biological wealth and community involvement must be optimally utilized to capture available opportunities, including increasing interest in nature-based tourism and government support. The recommended strategic priorities are improving facilities and infrastructure, strengthening the role of local communities, and promoting more effective development. This study contributes to the preservation of mangrove ecosystems and the development of sustainable ecotourism by planning strategies that consider environmental and socio-economic aspects. This study has limitations, including the small number of respondents and the survey’s limited scope, which was conducted only in one season. Consequently, the results do not accurately reflect the overall annual conditions. The study suggests further expanding the scope of the data and reviewing digital promotion strategies to expand the reach and participation of tourists